(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article outlines the state and main directions of digital transformation necessary to achieve the level of digital maturity of a general education organization. At the same time, in the context of the introduction of digital governance principles, the importance, essence and content of the digital transformation process and the features, problems arising in the process of digital transformation, as well as one of the risk reduction tools, are considered.